The effect on information technology infrastructure flexibility on intranet effectiveness - Masrek, Mohamad Noorman; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
When intranet was first conceived a decade ago, its adoption was only affordable by large business enterprise or organizations. However, at present, intranet adoption has become so prevalent that almost every organizations, irrespective of sizes and business nature has diffused intranet into their business operations and activities. While studies addressing the effectiveness of the intranet have been greatly reported in the literature, very few have really explored or focused on the antecedents or determinants to intranet effectiveness. Specifically, none has ever attempted to examine the effect of information technology (IT) infrastructure capabilities on intranet effectiveness. Against this concern, this study is an attempt to explore the relationship between IT infrastructure flexibility and intranet effectiveness. In addition, it also seeks to investigate the perceived level of IT infrastructure flexibility and intranet effectiveness in the context of public organizations in Malaysia. Based on the results of the analysis, this study has empirically showed that IT infrastructure flexibility comprising of connectivity and IT personnel are influential in determining intranet effectiveness measured in terms of operation, culture and facilitation.